Capital Theory and Investment Behavior - Jorgenson, Dale W. (American Economic Review, 1963)
Tax policy and investment behaviour: tax policy and the cost of capital services, estimates of the parameters of the investment function, the effects of tax policy on investment behaviour, Robert E. Hall and Dale W. Jorgenson application of the theory of optimum capital accumulation: theory of investment behaviour, econometrics of investment behaviour, estimates of the parameters of the investment functions, impact of tax policy on investment behaviour, Robert E. Hall and Dale W. Jorgenson technology and decision rules in the theory of investment behaviour: introduction, technology, objective function, optimal investment policy, decision rules, Dale W. Jorgenson the economic impact of investment incentives: introduction, postwar investment incentives in the United States, the economic analysis of investment incentives, current policy alternatives, direct impact, total impact, Dale W. Jorgenson the economic theory of replacement and depreciation: introduction, replacement, depreciation, form of the replacement distribution, Dale W. Jorgenson investment and production - a review: introduction, form of the production function - cross sections, form of the production function - time series, returns to scale, Dale W. Jorgenson the investment tax credit and counter-cyclical policy: summary, introduction, impact of the investment tax credit, alternative investment tax credits, appendices - the investment equation, optimization procedures, Roger H. Gordon and Dale W. Jorgenson inflation-proof depreciation of assets: the first-year system, administrative aspects, ... against two others, future economic impact, a better way, Alan J. Auerbach and Dale W. Jorgenson inflation and corporate capital recovery: introduction, theoretical frame-work, empirical implementation, capital recovery during the postwar period, proposed systems for capital recovery, Dale W. Jorgenson and Martin A. Sullivan the efficiency of capital allocation: introduction, technology and preferences, general equilibrium model, appendix - list of instrumental variables, Dale W. Jorgenson and Kun-Young Yun tax policy and capital allocation: introduction, tax policy, technology and preferences, general equilibrium model, tax reform, appendix - list of instrumental variables, Dale W. Jorgenson and Kun-Young Yun. (Part contents).